Quran music: Effective strategy in reducing depressive symptoms and increasing academic self-efficacy of dormitory student’s - reza mirarab razi; maryam talebi; alireza badele (Faṣlnāmah-i Farhang Mushavirah va Ravān/Darmānī, 2020)
Quran music: Effective strategy in reducing depressive symptoms and Increasing Academic Self-Efficacy on dormitory students Abstract Aim: The main goal of this research was to assess the effect of the holy Quran music on dormitory student’s depression. Method: using an experimental pretest- posttest- follow up with control group design, 40 dormitory students from Allameh Tabataba’i university that their depression level were more than average according to the Beck Depression Inventory (BDI)’s and Bandura Self-Efficacy Questionnaire score distribution selected and assigned to experimental (n=20) and control group (n=20) randomly. Experimental group listened to specific Quran Soreh (Rad, Shamsh and Maedeh) with the voice of Abdolbaset and Mostafa Esmaiel in 20 days (each day 20 minutes in two 10 minutes shifts), whereas control group have not been received any manipulation. The degree of two group depression was assessed after 20 days and two-month later. Also by conducting a self-efficacy questionnaire, the effect of the holy Quran music was also measured. Results: The results of analysis of covariance (ANCOVA) showed significant reduction in experimental group’s depression. The result of paired T test indicated that effectiveness of the holy Quran voice has been maintained Discussion: As increase self-efficacy the finding of current research supports the important of spirituality based therapies and religious therapy in curing psychological problems. Keywords: holy Quran, Quran music, Depression, Academic self-efficacy, dormitory students